Mindfulness mediates the relationship between cognitive reappraisal and resilience in higher education students. (1st April 2020) - Zarotti, Nicolò; Povah, Claire; Simpson, Jane
Abstract: Background: : associations between the constructs of cognitive reappraisal and resilience, in particular within the context of higher education (HE), have been consistently reported. Moreover, both constructs are strongly and positively associated with mindfulness, meaning that higher levels of mindfulness are found in people who are better at reappraising emotions and being resilient. However, no investigation has so far clarified the role that may mindfulness play in the relationship between cognitive reappraisal and resilience, especially within populations where a strong effect, such as for university students, is already evident. Aims: : the present study tested the hypothesis that mindfulness plays a mediational role in the association between cognitive reappraisal and psychological resilience. Sample: : this study involved a sample of 811 students enrolled at universities within the UK. Results: : the data confirmed the strong relationship between cognitive reappraisal and resilience, as well as each construct's individual association with mindfulness. In addition, mindfulness was a significant mediator of the relationship between cognitive appraisal and resilience, thus corroborating the study's main hypothesis. Conclusions: : as the concern around students' mental health grows bigger worldwide, these findings suggest that implementing mindfulness training programmes within HE should be given increasing consideration in the future.